Severity of psoriasis and its impact on patient-reported outcomes (PROs): real world evidence with brodalumab 210 mg from the LIBERO study - Matthias Augustin; Rudolf E. Schopf; Sven R. Quist; Nalan Kalyon; Ralph M. von Kiedrowski (Journal of Dermatological Treatment)
Aim Only limited data is available on the benefit of brodalumab 210 mg, an IL-17 receptor A antagonist, on patient-reported outcomes (PROs) in different psoriasis severity groups under real-world-evidence (RWE) conditions.Methods LIBERO, a prospective, multicenter, 12- and 52-weeks (W) non-interventional study on brodalumab in adult patients with plaque-type psoriasis assessed its short- and long-term impact on PROs in mild, moderate and severe psoriasis defined by Psoriasis Area Severity Index (PASI).Results 200 (31.3%) patients with severe (PASI ≥ 20), 263 (41.2%) with moderate (PASI = 10–19) and 168 (26.3%) with mild (PASI < 10) psoriasis were analyzed. In all severity groups a rapid and sustained reduction of mean(m) PASI was observed as of W2. 76.7, 84.9 and 82.0% of patients assessed their psoriasis as being clear/almost clear in mild, moderate and severe subgroups and mean Dermatological Life Quality Index improved from 11.2, 14.3 and 17.1 to 3.2, 2.9 and 3.8. 73.7% of patients rated brodalumab as being quite/very beneficial (Patient Benefit Index, PBI) and were quite/very satisfied with the treatment (TSQM-9). Regaining disease control and reducing physical impairment achieved highest PBI-scores.Conclusion LIBERO confirms the benefit of brodalumab on PROs including rapid and complete clearance of skin lesions, quality of life and individual patient benefits – irrespective of their disease severity.